COVID-19 laboratory diagnosis: comparative analysis of different RNA extraction methods for SARS-CoV-2 detection by two amplification protocols - Campos , Karoline Rodrigues (2021)
The gold standard for the laboratory diagnosis of COVID-19 is the reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) assay, which searches for SARS-CoV-2 target genes in nasopharyngeal/oropharyngeal (NP/OP) samples, and its performance depends on the quantity and quality of the RNA input. This study compared the performance and cost-effectiveness of three different kits/reagents for RNA extraction used in COVID-19 diagnosis in Sao Paulo, Brazil. A total of 300 NP/OP samples belonging to suspected cases of COVID-19 stored in a biorepository were randomly selected, and RNA was extracted using (i) automated extraction (Loccus, Extracta Kit FAST), (ii) manual extraction (BioGene Kit, Bioclin, Quibasa), and (iii) quick extraction methods (Lucigen, Quick DNA Extract Kit). Next, the samples were tested using RT-qPCR for SARS-CoV-2 with the Allplex 2019-nCoV modified assay and the Charité-Berlin protocol. All assays/kits were used according to the manufacturer’s instructions. For the Allplex kit, the sensitivity in detecting SARS-CoV-2 with previously extracted RNA by different procedures was 100.0% for Loccus, 100.0% for BioGene and 91.9% for Quick. Using the Charité-Berlin protocol, the sensitivities were 81.4% for Loccus, 81.2% for BioGene and 60.7% for Quick. The least sensitive target gene and the gene most affected by RNA extraction procedures was the RNA-dependent RNA polymerase gene (Charité-Berlin protocol). No false-positive SARS-CoV-2 results were detected using RNA obtained from any of the different protocols. In conclusion, Loccus and BioGene RNA extractions were efficient for RT-qPCR assays, and although the BioGene procedure is less expensive, Loccus is the best choice because it allows the rapid handling of hundreds or thousands of samples, a desirable feature during pandemics. Although less sensitive, the Quick extraction is useful during outbreaks coupled with the Allplex amplification kit for SARS-CoV-2 diagnosis (κ = 0.925).